Family social climate of women who consume addictive substances with and without the exercise of prostitution - Agama Hidalgo, Jenny Magaly (2019)
The purpose of this study is to relate the family functioning of consumers of addictive substances who practice prostitution with respect to consumers who do not practice prostitution and a control group who are not consumers or exercise alcohol. prostitution. The sample consisted of 148 women who were divided into three comparison groups that responded to the family social climate scale (FES), not finding significant differences between the group of women with and without exercise of prostitution, but with the control group.